Distance Learning Management in Elementary Schools During the Pandemic - Dwi Hariyanta; Hermanto Hermanto; Herwin Herwin (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2022)
This study aims to analyze the management of distance learning in elementary schools during the pandemic. This study is a phenomenological study conducted on distance learning conducted by primary school teachers during the pandemic. The subjects of this research are teachers who have conducted distance learning, students, and parents of students. Data collection is done by using interviews. The data analysis technique used is qualitative analysis through data collection, datacondensation, data presentation, and data verification. This study concludes that the planning for distance learning during the pandemic is done by choosing important competencies to be conveyed to students by paying attention to learning situations that must be delivered remotely. In the aspect of implementing distance learning, various techniques used by teachers are found in managing their learning. However, in general, all these managements utilize technology assistance in carrying out their learning, both synchronous and asynchronous. To obtain information related to the achievement of goals, the teacher evaluates distance learning by utilizing online applications that can be run both on smartphones and computer devices. This is done to obtain the results of the learning evaluation compliant with the material that has been delivered during the process of implementing distance learning.